Tradisi Membangun Rumah dengan Pendekatan Kearifan Lokal di Desa Tinabani Kabupaten Ende - Silvester M Siso; Fabiola T.A. Kerong (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
ABTRACT The purpose of this evaluation is to study the tradition of building houses and the values contained in the tradition. This research is descriptive with qualitative agreement. Researchers become the main source in obtaining data from the results of field analysis and interviews. The research location was in Tinabani Village, Ende District, Ende Regency. The intensive relationship between the people of Tinabani Village and their natural, social and historical environment has provided knowledge of the use of materials provided by nature for escaping purposes. From the social side it is known how the Tinabani people work hand in hand in the process of making a house. This attitude of mutual cooperation makes the community more harmonious and peaceful. Meanwhile, history recognizes the traditions and traditions that bind their lives. It can be concluded that the people of Tinabani Village make good use of nature to preserve history. Tinabani people have strong traditions and social relations. Keywords; Tradition, Home, Local Wisdom, Tinabani